Method for manufacturing adhesive sheet and method for manufacturing optical film with adhesive sheet
Patent Information
- Application Number
- JP2022117589
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-07-22
- Publication Date
- 2025-01-31
AI Technical Summary
The issue of residual monomer odor and reduced anchoring force in adhesive sheets used in optical laminates is addressed by controlling curing conditions alone is insufficient.
Performing surface modification treatment using active energy rays on adhesive sheets containing monomer polymers and residual monomers to reduce residual monomer content while maintaining anchoring force.
The method effectively reduces residual monomer content to 5000 ppm or less and enhances anchoring force, improving the quality and performance of adhesive sheets in optical laminates.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a pressure-sensitive adhesive sheet and a method for producing an optical film with a pressure-sensitive adhesive sheet. [Background technology]
[0002] Various image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices, generally include an optical laminate including an optical film such as a polarizing film and an adhesive sheet. An adhesive sheet is usually used for bonding between the optical films included in the optical laminate, or for bonding between the optical laminate and an image display panel. A typical adhesive sheet is a sheet obtained by curing a monomer group including an acrylic monomer, a silicone monomer, etc., by polymerization and crosslinking. Patent Document 1 discloses a method (photocuring method) for forming an adhesive sheet by irradiating a coating layer including a photocurable composition with light. Patent Document 1 also discloses a method for reducing the amount of monomer remaining in the formed adhesive sheet by heating and drying. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 4822034 Summary of the Invention [Problem to be solved by the invention]
[0004] When the amount of residual monomer contained in the cured pressure-sensitive adhesive sheet becomes large, a problem of odor (monomer odor) occurs. For example, it is possible to reduce the amount of residual monomer by controlling the curing conditions. However, according to the study by the present inventors, when the amount of residual monomer is reduced only by controlling the curing conditions, the anchoring force of the pressure-sensitive adhesive sheet to the object to be joined may decrease.
[0005] An object of the present invention is to provide a technique suitable for producing a PSA sheet in which the amount of residual monomer is reduced and the decrease in anchoring power is inhibited. [Means for solving the problem]
[0006] The present invention relates to a method for producing a pressure-sensitive adhesive sheet, the method comprising: subjecting a first pressure-sensitive adhesive sheet, which comprises a polymer of a monomer and a residual monomer, to a surface modification treatment using active energy rays to obtain a second pressure-sensitive adhesive sheet in which the amount of the residual monomer is reduced compared to that of the first pressure-sensitive adhesive sheet; to provide.
[0007] In another aspect, the present invention provides a method for producing a composition comprising: A method for producing an optical film with a pressure-sensitive adhesive sheet, comprising: arranging an optical film on a surface of the second pressure-sensitive adhesive sheet formed by the pressure-sensitive adhesive sheet production method of the present invention to form an optical film with a pressure-sensitive adhesive sheet; to provide. Effect of the Invention
[0008] According to the present invention, a technique suitable for producing a PSA sheet in which the amount of residual monomer is reduced and a decrease in anchoring power is suppressed can be provided. [Brief description of the drawings]
[0009] [Figure 1] 1A to 1C are schematic diagrams illustrating an example of a method for producing a pressure-sensitive adhesive sheet of the present invention. [Diagram 2] 1A to 1C are schematic diagrams illustrating an example of a method for producing a pressure-sensitive adhesive sheet of the present invention. [Figure 3A] FIG. 2 is a schematic diagram illustrating an example of a method for forming a first adhesive sheet. [Figure 3B] FIG. 2 is a schematic diagram illustrating an example of a method for forming a first adhesive sheet. [Figure 3C] FIG. 2 is a schematic diagram illustrating an example of a method for forming a first adhesive sheet. [Figure 4]1A to 1C are schematic diagrams illustrating an example of a method for producing a pressure-sensitive adhesive sheet of the present invention. [Diagram 5] FIG. 2 is a schematic diagram for explaining an example of a method for producing an optical film with a pressure-sensitive adhesive sheet of the present invention. [Figure 6] FIG. 2 is a schematic diagram for explaining an example of a method for producing an optical film with a pressure-sensitive adhesive sheet of the present invention. [Figure 7] FIG. 2 is a schematic diagram for explaining an example of a method for producing an optical film with a pressure-sensitive adhesive sheet of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] A method for producing a pressure-sensitive adhesive sheet according to a first aspect of the present invention includes the steps of: The method includes performing a surface modification treatment using active energy rays on a first adhesive sheet containing a polymer of a monomer and a residual monomer, thereby obtaining a second adhesive sheet in which the amount of the residual monomer is reduced compared to the first adhesive sheet.
[0011] In a second aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to the first aspect, the amount of the residual monomer in the second pressure-sensitive adhesive sheet is 5000 ppm (by weight) or less.
[0012] In a third aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to the first or second aspect, the amount of the residual monomer in the first pressure-sensitive adhesive sheet is 6000 ppm (by weight) or more.
[0013] In a fourth aspect of the present invention, for example in the method for producing a pressure-sensitive adhesive sheet according to any one of the first to third aspects, the surface modification treatment is at least one selected from the group consisting of corona treatment, plasma treatment, excimer UV light treatment and frame treatment.
[0014] In a fifth aspect of the present invention, for example in the method for producing a pressure-sensitive adhesive sheet according to any one of the first to fourth aspects, the surface modification treatment is carried out in an atmosphere with an oxygen concentration of 20% by volume or less.
[0015] In a sixth aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to the fifth aspect, the atmosphere is an inert gas atmosphere.
[0016] In a seventh aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to any one of the first to sixth aspects, the surface modification treatment is carried out on an exposed surface of the first pressure-sensitive adhesive sheet.
[0017] In an eighth aspect of the present invention, for example in the method for producing an adhesive sheet according to any one of the first to seventh aspects, the first adhesive sheet is an adhesive sheet formed from a photocurable composition containing a group of monomers and / or a partial polymer of the group of monomers.
[0018] In a ninth aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to the eighth aspect, the group of monomers includes a (meth)acrylic monomer.
[0019] In a tenth aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to any one of the first to ninth aspects, the method further comprises forming the first pressure-sensitive adhesive sheet by irradiating light to a coating layer comprising a photocurable composition containing a group of monomers and / or a partial polymer of the group of monomers.
[0020] In an eleventh aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to the tenth aspect, the first pressure-sensitive adhesive sheet is formed by irradiating the light to a laminate comprising a base sheet, the coating layer, and a release liner in this order.
[0021] In a twelfth aspect of the present invention, for example in the method for producing a pressure-sensitive adhesive sheet according to the tenth or eleventh aspect, the light is different from the active energy rays.
[0022] A method for producing an optical film with a pressure-sensitive adhesive sheet according to a thirteenth aspect of the present invention comprises the steps of: The method includes forming an optical film with a pressure-sensitive adhesive sheet by arranging an optical film on a surface of the second pressure-sensitive adhesive sheet formed by the manufacturing method according to any one of the first to twelfth aspects.
[0023] In a fourteenth aspect of the present invention, for example, in the method for producing an optical film with a pressure-sensitive adhesive sheet according to the thirteenth aspect, the surface is a surface that has been subjected to the surface modification treatment.
[0024] In a fifteenth aspect of the present invention, for example, in the method for producing an optical film attached with a pressure-sensitive adhesive sheet according to the thirteenth or fourteenth aspect, the optical film includes at least one film selected from the group consisting of a polarizing film and a retardation film.
[0025] In a 16th aspect of the present invention, for example, in a method for manufacturing an optical film with an adhesive sheet according to any one of the 13th to 15th aspects, an optical film with an adhesive sheet is formed in which the anchoring force of the second adhesive sheet to the optical film is 12 N / 25 mm or more.
[0026] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified in any manner without departing from the gist of the present invention.
[0027] The present inventors came up with the idea of reducing the amount of residual monomers by subjecting a pressure-sensitive adhesive sheet to a surface modification treatment using active energy rays, and conducted further research based on this idea, leading to the completion of the present invention. By subjecting a pressure-sensitive adhesive sheet to a surface modification treatment using active energy rays, the amount of residual monomers contained therein can be reduced and a decrease in anchoring strength can be suppressed.
[0028] [Method of manufacturing adhesive sheet] An example of the method for producing the pressure-sensitive adhesive sheet of the present invention will be described with reference to FIG. 1. In this example, a second pressure-sensitive adhesive sheet 2 is formed by performing a surface modification treatment using active energy rays 21 on a first pressure-sensitive adhesive sheet 1. The first pressure-sensitive adhesive sheet 1 contains a polymer of a monomer and a residual monomer. The residual monomer is typically an unreacted monomer in a polymerization reaction that forms a polymer. In the second pressure-sensitive adhesive sheet 2, the amount of the residual monomer is reduced compared to the first pressure-sensitive adhesive sheet 1. The surface modification treatment is actually performed on the surface 12 of the first pressure-sensitive adhesive sheet 1, which is the exposed surface. More specifically, the surface modification treatment is performed by irradiating the surface 12 with active energy rays 21. However, as long as the active energy rays 21 are used, the aspect of the surface modification treatment is not limited to this example. In addition, the surface modification treatment is performed on one surface 12 of the first pressure-sensitive adhesive sheet 1. However, the surface modification treatment may be performed on both surfaces 12, 13 of the first pressure-sensitive adhesive sheet 1. The surface 12 on which the surface modification treatment has been performed becomes the modified treatment surface 14.
[0029] Another example of the method for producing a pressure-sensitive adhesive sheet of the present invention will be described with reference to Fig. 2. In this example, a surface modification treatment is performed on a long first pressure-sensitive adhesive sheet 1 using active energy rays 21 to form a long second pressure-sensitive adhesive sheet 2. The surface modification treatment is performed when the first pressure-sensitive adhesive sheet 1 passes through a treatment device 22. The surface modification treatment is also performed while the first pressure-sensitive adhesive sheet 1 and the second pressure-sensitive adhesive sheet 2 are transported in a state where they are laminated on a long base sheet 11. The method of Fig. 2 is particularly suitable for mass production of the second pressure-sensitive adhesive sheet 2.
[0030] The amount of residual monomer in the second adhesive sheet 2 may be 5000 ppm or less, 4500 ppm or less, 4000 ppm or less, 3500 ppm or less, 3000 ppm or less, 2500 ppm or less, 2000 ppm or less, 1500 ppm or less, or even 1000 ppm or less. The lower limit of the amount of residual monomer is, for example, 30 ppm or more. In this specification, "ppm" is always based on weight.
[0031] The amount of residual monomer in the first pressure-sensitive adhesive sheet 1 may be, for example, 6000 ppm or more, 8000 ppm or more, 10000 ppm or more, 13000 ppm or more, 15000 ppm or more, 18000 ppm or more, 20000 ppm or more, 25000 ppm or more, 30000 ppm or more, 35000 ppm or more, or even 40000 ppm or more. The upper limit of the amount of residual monomer is, for example, 50000 ppm or less.
[0032] The amount of residual monomer in the first pressure-sensitive adhesive sheet 1 and the second pressure-sensitive adhesive sheet 2 can be evaluated by gas chromatogram (GC) analysis.
[0033] The surface modification treatment is, for example, at least one selected from the group consisting of corona treatment, plasma treatment, excimer UV light treatment, and flame treatment, and may be corona treatment and / or plasma treatment, or may be corona treatment. In other words, the active energy rays 21 may be at least one selected from the group consisting of electron beams, ion beams, plasma beams, and ultraviolet rays. Each surface modification treatment can be performed by a corresponding known treatment device 22.
[0034] The surface modification treatment can be performed in an air atmosphere, but may be performed in an atmosphere with an oxygen concentration reduced compared to air (oxygen concentration 20.9% by volume). The surface modification treatment in an atmosphere with a reduced oxygen concentration is particularly suitable for reducing the amount of residual monomers while suppressing the degree of treatment. The surface modification treatment may be performed in an atmosphere with an oxygen concentration of 20% by volume or less, 15% by volume or less, 10% by volume or less, 8% by volume or less, 6% by volume or less, 5% by volume or less, 3% by volume or less, 1% by volume or less, 0.5% by volume or less, or even 0.3% by volume or less. The lower limit of the oxygen concentration may be 0.01% by volume or more, 0.1% by volume or more, or even 0.5% by volume or more. An example of an atmosphere with a reduced oxygen concentration is a mixed atmosphere of oxygen and an inert gas. Examples of the inert gas are argon and nitrogen. However, the inert gas is not limited to the above examples. The anchoring force of the modified surface 14 of the second pressure-sensitive adhesive sheet 2 can be improved by the surface modification treatment compared to before the treatment. Surface modification treatment in an atmosphere with a reduced oxygen concentration is particularly effective when the degree of treatment is increased (for example, when the discharge amount is 10 kJ / m in corona treatment). 2 The surface modification treatment is particularly suitable for increasing the anchoring power of the modified surface 14 when the surface modification treatment is performed at a temperature of 100° C. or more. The anchoring power is, for example, the anchoring power for a resin film such as an optical film. In addition, depending on the type of surface modification treatment, the risk of fire can be reduced even when the degree of treatment is increased by performing the treatment in an atmosphere with a reduced oxygen concentration.
[0035] The surface modification treatment may be carried out in an atmosphere substantially free of oxygen. Substantially free of oxygen means that the oxygen concentration is less than 0.1% by volume, preferably less than 0.05% by volume, and more preferably less than 0.01% by volume. An example of an atmosphere substantially free of oxygen is an inert gas atmosphere. In other words, the surface modification treatment may be carried out in an inert gas atmosphere. The surface modification treatment may be carried out under normal pressure (1 atm).
[0036] The conditions for the surface modification treatment, which is a corona treatment, are expressed in terms of the discharge amount, for example, 0.6 to 100 kJ / m 2 The lower limit of the discharge amount is 1 kJ / m 2 More than 2kJ / m 2 More than 5kJ / m2 More than 7kJ / m 2 More than 10kJ / m 2 More than 13kJ / m 2 More than 15kJ / m 2 More than 20kJ / m 2 More than 25kJ / m 2 More than 30kJ / m 2 or more, 35 kJ / m 2 The upper limit of the discharge amount is 70 kJ / m 2 Below, 60kJ / m 2 Below, 50kJ / m 2 Below, 45kJ / m 2 Below, 40kJ / m 2 Below, 30kJ / m 2 Below, 20kJ / m 2 Below that, even 18kJ / m 2 When the corona treatment is performed in an atmosphere with an oxygen concentration of 10% by volume or more and 20.9% by volume or less, the discharge amount is 1 to 18 kJ / m 2 When the corona treatment is performed in an atmosphere with an oxygen concentration of 0.01% by volume or more and less than 10% by volume, the discharge amount is 1 to 60 kJ / m 2 may be also possible.
[0037] An example of the base sheet 11 is the same as an example of the base sheet 31 described below that can be used to form the first adhesive sheet 1. The base sheet 31 used to form the first adhesive sheet 1 may be used as the base sheet 11.
[0038] (First adhesive sheet) The first adhesive sheet 1 may be an adhesive sheet (photocurable adhesive sheet) formed from a photocurable composition containing a monomer group and / or a partial polymer of the monomer group. However, the first adhesive sheet 1 is not limited to the above example as long as it contains a polymer of a monomer and a residual monomer. The first adhesive sheet 1 may be an adhesive sheet (thermosetting adhesive sheet) formed from a thermosetting composition containing a monomer group and a solvent. The amount of residual monomer contained tends to be greater in a photocurable adhesive sheet than in a thermosetting adhesive sheet. This may be due to the fact that oxygen in the air tends to inhibit the curing of the photocurable composition, especially in the vicinity of the surface of the sheet. For this reason, in a photocurable adhesive sheet, the residual monomer tends to move to the outside of the adhesive sheet, typically to an adjacent layer, causing adverse effects. One example of an adverse effect is the occurrence of cracks in an adjacent optical film. From this viewpoint, when the first adhesive sheet 1 (and the second adhesive sheet 2 formed from the adhesive sheet) are photocurable, the manufacturing method of the present invention is particularly advantageous.
[0039] The photocurable first adhesive sheet 1 can be formed, for example, by irradiating light 35 to a first laminate 34 including, in this order, a base sheet 31, a coating layer 32 containing a photocurable composition, and a release liner 33 (FIG. 3A). The first adhesive sheet 1 is formed from the coating layer 32 by irradiation with light 35 (FIG. 3C). The formed first adhesive sheet 1 is sandwiched between the base sheet 31 and the release liner 33 and constitutes a part of the second laminate 36 until the release liner 33 is peeled off. In the example of FIG. 3A, the light 35 is irradiated from the side of the base sheet 31. The light 35 penetrates the base sheet 31 to reach the coating layer 32 and cure the coating layer 32. However, the light 35 may be irradiated from the side of the release liner 33, or from both the side of the release liner 33 and the base sheet 31 (FIG. 3B).
[0040] The manufacturing method of the present invention may further include the above-mentioned step of forming a first pressure-sensitive adhesive sheet 1. In other words, the manufacturing method of the present invention may further include forming the first pressure-sensitive adhesive sheet 1 by irradiating light 35 to a coating layer 32 containing a photocurable composition containing a group of monomers and / or a partial polymer of the group of monomers. In this case, the first pressure-sensitive adhesive sheet 1 may be formed by irradiating light 35 to a first laminate 34 containing, in this order, a base sheet 31, a coating layer 32, and a release liner 33. The step of forming the first pressure-sensitive adhesive sheet 1 and the above-mentioned surface modification treatment of the formed first pressure-sensitive adhesive sheet 1 may be carried out consecutively.
[0041] With reference to FIG. 4, an example of the manufacturing method of the present invention further including a step of forming a first pressure-sensitive adhesive sheet 1 will be described. In this example, a coating layer 32 of a photocurable composition is formed on one side of a long base sheet 31 unwound from a roll 41 by a coating device 42. Next, a long release liner 33 unwound from a roll 43 is placed on the coating layer 32 to form a long first laminate 34. Next, light 35 is irradiated from an irradiation device 44 to the first laminate 34 to form a long first pressure-sensitive adhesive sheet 1. Next, the release liner 33 is peeled off from a second laminate 36 including the first pressure-sensitive adhesive sheet 1 and wound up on a roll 45. The above steps are performed while the base sheet 31 and the release liner 33 are being transported. Next, a surface modification treatment is performed by a treatment device 22 on the exposed surface (surface 12) of the first pressure-sensitive adhesive sheet 1 formed by peeling off the release liner 33 to form a second pressure-sensitive adhesive sheet 2 having a modified surface 14. The above steps after peeling off release liner 33 are carried out while transporting base sheet 31(11). The method of FIG.
[0042] <Release liner> An example of the substrate of the release liner 33 (hereinafter, "liner substrate") is a resin film. Examples of resins that may be contained in the liner substrate are polyesters such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyethersulfone, polycarbonate, polyamide, polyimide, polyolefin, (meth)acrylic resins, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyvinyl alcohol, polyarylate, and polyphenylene sulfide. The resin is preferably a polyester such as polyethylene terephthalate.
[0043] The release liner 33 may have transparency to light 35 , and may have the same degree of transparency to light 35 as the base sheet 31 .
[0044] The thickness of the release liner 33 is, for example, 10 to 200 μm, and may be 25 to 150 μm.
[0045] The release liner 33 may include a layer other than the liner substrate. The release liner 33 may include a release layer. The release liner 33 includes, for example, a liner substrate and a release layer formed on one surface of the liner substrate. This release liner 33 can be used such that the release layer is on the coating layer 32 side.
[0046] The release layer is typically a cured layer of a release agent composition containing a release agent. As the release agent, various types of release agents can be used, such as silicone-based release agents, fluorine-based release agents, long-chain alkyl-based release agents, fatty acid amide-based release agents, and silica powder. The release liner 33 may be provided with a cured layer of a release agent composition containing a silicone-based release agent as a main component (hereinafter, "silicone release layer"). The silicone release layer is particularly suitable for achieving both adhesion to the first pressure-sensitive adhesive sheet 1 and releasability. In this specification, the main component means the component with the largest content.
[0047] The silicone-based release agent is, for example, various types of curable silicone materials such as addition reaction type, condensation reaction type, ultraviolet curable type, electron beam curable type, and solventless type, and an addition reaction curable silicone material is preferred. An addition reaction curable silicone material is particularly suitable for forming a release layer that has both adhesion and releasability to the first adhesive sheet 1. The curable silicone material may be a silicone-modified resin in which reactive silicone is introduced into an organic resin such as urethane, epoxy, or alkyd resin by graft polymerization or the like.
[0048] An example of the addition reaction curing silicone material is a polyorganosiloxane having a vinyl group or an alkenyl group in the molecule. The addition reaction curing silicone material may not have a hydrosilyl group. Examples of the alkenyl group are 3-butenyl, 4-pentenyl, 5-hexenyl, 6-heptenyl, 7-octenyl, 8-nonenyl, 9-decenyl, 10-undecenyl, and 11-dodecenyl. Examples of the polyorganosiloxane are polyalkylalkylsiloxanes such as polydimethylsiloxane, polydiethylsiloxane, and polymethylethylsiloxane, polyalkylarylsiloxane, and copolymers of multiple types of Si atom-containing monomers such as poly(dimethylsiloxane-diethylsiloxane). The polyorganosiloxane is preferably polydimethylsiloxane.
[0049] A release agent composition containing a silicone-based release agent as a main component (hereinafter referred to as "silicone release agent composition") usually contains a crosslinking agent. An example of the crosslinking agent is polyorganosiloxane having a hydrosilyl group. The crosslinking agent may have two or more hydrosilyl groups in one molecule.
[0050] The silicone release agent composition may contain a curing catalyst. An example of the curing catalyst is a platinum catalyst. An example of the platinum catalyst is chloroplatinic acid, an olefin complex of platinum, or an olefin complex of chloroplatinic acid. The amount of the platinum catalyst used is, for example, 10 to 1000 ppm (weight basis, platinum equivalent) based on the total solid content of the composition.
[0051] The silicone release agent composition may contain additives. Examples of additives are release control agents and adhesion promoters. Examples of release control agents are unreactive silicone resins, and more specific examples are organosiloxanes such as octamethylcyclotetrasiloxane, and MQ resins. The amount of the release control agent and adhesion promoter used is, for example, 1 to 30% by weight in total based on the total solid content of the composition. Further examples of additives are fillers, antistatic agents, antioxidants, ultraviolet absorbers, plasticizers, and colorants. The amount of the further additives used is, for example, 10% by weight or less in total based on the total solid content of the composition.
[0052] The silicone release agent composition may contain an organic solvent. Examples of the organic solvent include hydrocarbon solvents such as cyclohexane, n-hexane, and n-heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; and alcohol solvents such as methanol, ethanol, and butanol. Two or more organic solvents may be contained. The amount of the organic solvent used is preferably 80 to 99.9% by weight of the silicone release agent composition.
[0053] The release layer can be formed, for example, by heating and drying a coating film containing the release agent composition formed on a liner substrate. Various coating methods such as roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, and die coating can be applied to apply the release agent composition. For example, hot air drying can be applied to apply the heating and drying. The heating temperature and time vary depending on the heat resistance of the liner substrate, but are usually about 80 to 150°C and 10 seconds to 10 minutes. If necessary, irradiation with active energy rays such as ultraviolet rays may be used in combination.
[0054] The thickness of the release layer is, for example, 10 to 300 nm. The upper limit of the thickness may be 200 nm or less, 150 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, less than 100 nm, 90 nm or less, 80 nm or less, 70 nm or less, less than 70 nm, or even 65 nm or less. The lower limit of the thickness may be 15 nm or more, 20 nm or more, 25 nm or more, 30 nm or more, 35 nm or more, 40 nm or more, 45 nm or more, or even 50 nm or more.
[0055] The release liner 33 may be in the form of a sheet or a continuous piece.
[0056] <Base sheet> An example of the base sheet 31 is a resin film. Examples of the resin contained in the base sheet 31 are the same as the examples of the resin that can be contained in the liner base material.
[0057] The base sheet 31 preferably has excellent light 35 transmittance.
[0058] The thickness of the base sheet 31 is, for example, 10 to 200 μm, and may be 25 to 150 μm.
[0059] The base sheet 31 may have a release layer on the surface on the side of the coating layer 32. Examples of the release layer that the base sheet 31 may have and the manufacturing method thereof are the same as the examples of the release layer that the release liner 33 may have and the manufacturing method thereof. Both the release liner 33 and the base sheet 31 may have a release layer. In this case, both release layers may be formed from a release agent composition containing the same release agent as a main component. In addition, the thicknesses of both release layers may be different, and for example, the release layer provided on the base sheet 31 may be thicker.
[0060] For base sheet 31 , a sheet having a greater peel strength from first pressure-sensitive adhesive sheet 1 than release liner 33 can usually be selected.
[0061] The base sheet 31 may be in the form of a sheet or a continuous length.
[0062] <Photocurable composition> The photocurable composition is a composition that can form the first adhesive sheet 1 from the coating layer 32 by irradiation with light 35. The photocurable composition contains, for example, a monomer group containing a (meth)acrylic monomer and / or a partial polymer of the monomer group. The content of the (meth)acrylic component in the photocurable composition, i.e., the (meth)acrylic monomer and its partial polymer, may be 50% by weight or more, 60% by weight or more, 70% by weight or more, or even 80% by weight or more. In this case, an acrylic adhesive sheet containing a (meth)acrylic polymer and its crosslinked product as the main components can be formed. However, the photocurable composition is not limited to the above examples. In this specification, (meth)acrylic means acrylic and methacrylic. (Meth)acrylate means acrylate and methacrylate.
[0063] An example of the (meth)acrylic monomer is a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 20 carbon atoms on the side chain. The number of carbon atoms in the alkyl group may be 7 or less, 6 or less, 5 or less, or even 4 or less. The alkyl group may be linear or branched. Examples of the (meth)acrylic acid alkyl ester include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and the like. acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate (lauryl (meth)acrylate), n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate and octadecyl (meth)acrylate. The (meth)acrylic acid alkyl ester may be n-butyl (meth)acrylate.
[0064] The content of the (meth)acrylic acid alkyl ester in the monomer group is, for example, 40% by weight or more, and may be 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, or even 95% by weight or more. In calculating the content, the weight of the partially polymerized product is converted into the weight of each monomer before polymerization.
[0065] The monomer group may contain a carboxyl group-containing monomer. The carboxyl group-containing monomer may be a (meth)acrylic monomer, in other words, the (meth)acrylic monomer may contain a carboxyl group-containing monomer. Examples of the carboxyl group-containing monomer are (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. The content of the carboxyl group-containing monomer in the monomer group may be, for example, 10% by weight or less, 9% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, 5.5% by weight or less, or even 5% by weight or less. The lower limit of the content may be, for example, 0.1% by weight or more, 0.5% by weight or more, or even 1% by weight or more. The monomer group may not contain a carboxyl group-containing monomer.
[0066] The monomer group may contain a hydroxyl group-containing monomer. The hydroxyl group-containing monomer may be a (meth)acrylic monomer, in other words, the (meth)acrylic monomer may contain a hydroxyl group-containing monomer. The hydroxyl group-containing monomer may contribute to improving the cohesive strength of the pressure-sensitive adhesive sheet. Examples of the hydroxyl group-containing monomer are 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)-methyl acrylate. The hydroxyl group-containing monomer is preferably 2-hydroxyethyl (meth)acrylate or 4-hydroxybutyl (meth)acrylate. The content of the hydroxyl group-containing monomer in the monomer group is, for example, 5% by weight or less, and may be 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, 0.8% by weight or less, 0.5% by weight or less, 0.3% by weight or less, 0.2% by weight or less, or even 0.1% by weight or less. The lower limit of the content may be, for example, 0.01% by weight or more, 0.03% by weight or more, or even 0.05% by weight or more. The monomer group may not contain a hydroxyl group-containing monomer.
[0067] In the photocurable composition, each of the above-mentioned monomers may be contained as a partial polymer. The partial polymer may be either a homopolymer or a copolymer. The partial polymer can contribute to the stable formation of the coating layer 32 by appropriately increasing the viscosity of the photocurable composition.
[0068] The photocurable composition usually contains a photopolymerization initiator. An example of the photopolymerization initiator is a photoradical generator that generates radicals when exposed to visible light and / or ultraviolet light having a wavelength shorter than 450 nm.
[0069] Examples of photopolymerization initiators include benzoin ethers such as benzoin methyl ether, benzoin isopropyl ether, and benzil dimethyl ketal; substituted benzoin ethers such as anisole methyl ether; substituted acetophenones such as 2,2-diethoxyacetophenone and 2,2-dimethoxy-2-phenylacetophenone; α-hydroxyalkylphenones such as 1-hydroxycyclohexyl-phenyl ketone; substituted alpha-ketol such as 2-methyl-2-hydroxypropiophenone; aromatic sulfonyl chlorides such as 2-naphthalenesulfonyl chloride; photoactive oximes such as 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime; and benzophenone compounds such as benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, and 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone. Thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, 2,4-diethylthioxanthone and other thioxanthone compounds; 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine , 2-piperonyl-4,6-bis(trichloromethyl)-s-triazine, 2,4-bis(trichloromethyl)-6-styryl-s-triazine, 2-(naphth-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxy-naphth-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2,4-trichloromethyl-(piperonyl)-6-triazine, 2,4-trichloromethyl-(4'-methoxystyryl)-6-triazine and other triazine-based compounds;Oxime ester compounds such as 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], O-(acetyl)-N-(1-phenyl-2-oxo-2-(4'-methoxy-naphthyl)ethylidene)hydroxylamine; phosphine compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide; quinone compounds such as 9,10-phenanthrenequinone, camphorquinone, ethylanthraquinone; borate compounds; carbazole compounds; imidazole compounds; and titanocene compounds. The photocurable composition may contain one or more photopolymerization initiators.
[0070] The amount of the photopolymerization initiator in the photocurable composition is, for example, 0.02 to 10 parts by weight, and may be 0.05 to 5 parts by weight, based on 100 parts by weight in total of the monomer group and the partial polymer thereof.
[0071] The photocurable composition may contain a crosslinking agent. An example of the crosslinking agent is a polyfunctional monomer having two or more polymerizable functional groups in one molecule. The polyfunctional monomer may be a (meth)acrylic monomer. An example of the polyfunctional monomer is a monomer having two or more C=C bonds in one molecule, and a monomer having one or more C=C bonds and one or more polymerizable functional groups such as epoxy groups, aziridine groups, oxazoline groups, hydrazine groups, methylol groups, etc. in one molecule. The polyfunctional monomer is preferably a monomer having two or more C=C bonds in one molecule.
[0072] Examples of polyfunctional monomers include (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol diacrylate (N DDA), 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, and other polyfunctional acrylates (such as ester compounds of polyhydric alcohols and (meth)acrylic acid); allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, butyl di(meth)acrylate, and hexyl di(meth)acrylate. The polyfunctional monomer is preferably a polyfunctional acrylate, and more preferably trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0073] The amount of the crosslinking agent to be added varies depending on the molecular weight, the number of functional groups, etc., but may be, for example, 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or even 0.5 parts by weight or less per 100 parts by weight of the total of the monomer group and its partial polymer. The lower limit of the amount to be added is, for example, 0.01 parts by weight or more, and may also be 0.05 parts by weight or more.
[0074] The photocurable composition may contain additives other than those described above. Examples of the additives include a chain transfer agent, a silane coupling agent, a viscosity modifier, a tackifier, a plasticizer, a softener, an antiaging agent, a filler, a colorant, an antioxidant, a surfactant, an antistatic agent, and an ultraviolet absorbing agent.
[0075] The content of the solvent in the photocurable composition is, for example, 5% by weight or less, and may be 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, or even 0.5% by weight or less. The photocurable composition may be substantially free of a solvent. The phrase "substantially free of a solvent" means that the solvent derived from additives or the like is allowed to be present at a content of, for example, 0.1% by weight or less, preferably 0.05% by weight or less, and more preferably 0.01% by weight or less.
[0076] The viscosity of the photocurable composition is preferably 5 to 100 poise. A photocurable composition having a viscosity in the above range is particularly suitable for forming the coating layer 32.
[0077] <First laminate> The first laminate 34 can be formed, for example, by forming a coating layer 32 on a base sheet 31 (or a release liner 33) and then disposing a release liner 33 (or a base sheet 31) on the formed coating layer 32. Alternatively, the first laminate 34 may be formed by applying the photocurable composition in a pouring manner into the space between the base sheet 31 and the release liner 33 that are held at a predetermined distance such that their main surfaces face each other.
[0078] The coating layer 32 can be formed by various coating methods such as roll coating, kiss roll coating, gravure coating, reverse coating, roll brush, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, and die coating.
[0079] The thickness of coating layer 32 can be adjusted depending on the desired thickness of second adhesive sheet 2, and may be, for example, 5 to 100 μm, 5 to 50 μm, 5 to 25 μm, or even 5 to 20 μm.
[0080] The first laminate 34 may include an additional layer other than the base sheet 31, the coating layer 32, and the release liner 33. The additional layer may be disposed on the side of the base sheet 31 and / or the release liner 33 opposite to the side of the coating layer 32. The coating layer 32 is preferably in contact with the base sheet 31 and the release liner 33.
[0081] <Light irradiation> The light 35 irradiated to the first laminate 34 is, for example, visible light or ultraviolet light having a wavelength shorter than 450 nm. The light 35 may contain light having a wavelength in the same range as the absorption wavelength of the photopolymerization initiator contained in the photocurable composition. The light 35 may be irradiated with short-wavelength light having a wavelength of 200 nm or less, preferably 300 nm or less, cut by a filter or the like, and cutting short-wavelength light is suitable for suppressing deterioration of the base sheet 31 and / or the release liner 33 caused by the light 35. The light source of the light 35 is, for example, a light irradiation device equipped with an ultraviolet irradiation lamp. Examples of the ultraviolet irradiation lamp are ultraviolet LED, low-pressure mercury lamp, medium-pressure mercury lamp, high-pressure mercury lamp, ultra-high-pressure mercury lamp, metal halide lamp, xenon lamp, microwave-excited mercury lamp, black light lamp, chemical lamp, germicidal lamp, low-pressure discharge mercury lamp, and excimer laser. Two or more ultraviolet irradiation lamps may be combined.
[0082] The irradiation with light 35 may be continuous or intermittent.
[0083] The irradiation intensity of the light 35 is, for example, 1 to 20 mW / cm 2 The irradiation time of the light 35 is, for example, 5 minutes to 5 hours. The integrated light amount of the light 35 on the first laminate 34 is, for example, 100 to 5000 mJ / cm 2 2 It is.
[0084] The light 35 may be different from the active energy rays 21. For example, the light 35 and the active energy rays 21 may be different in type. The active energy rays 21, which are light, and the light 35 may be different in wavelength. When the active energy rays 21 are ultraviolet rays, the wavelength may be 200 nm or less.
[0085] The polymerization rate of the monomer group in the first adhesive sheet 1 is preferably 90% or more. The polymerization rate may be 95% or more, 96% or more, 97% or more, or even 98% or more.
[0086] The gel fraction of the first adhesive sheet 1 is, for example, 50% or more, and may be 75% or more, 80% or more, or even 85% or more.
[0087] The peel strength of release liner 33 to first adhesive sheet 1 may be smaller than the peel strength of base sheet 31 to first adhesive sheet 1 .
[0088] (Second adhesive sheet) The second adhesive sheet 2 may be of a photocurable type.
[0089] The thickness of the second adhesive sheet 2 is, for example, 2 to 70 μm, and may be 2 to 50 μm, 5 to 40 μm, 10 to 30 μm, 10 to 25 μm, or even 10 to 20 μm.
[0090] The gel fraction of second adhesive sheet 2 is, for example, 50% or more, and may be 75% or more, 80% or more, or even 85% or more.
[0091] The second adhesive sheet 2 can be used, for example, in an optical laminate including an optical film. In other words, the second adhesive sheet 2 may be for an optical laminate. The optical laminate may be an optical film with an adhesive sheet. The second adhesive sheet 2 may be used so that the modified surface 14 faces the optical film, or may be used so that it is in contact with the optical film. However, the purpose and method of use of the second adhesive sheet 2 are not limited to the above examples.
[0092] [Method of manufacturing optical film with adhesive sheet] With reference to FIG. 5, an example of the manufacturing method of the optical film with adhesive sheet of the present invention will be described. In this example, an optical film 3 is placed on the modified surface 14 of the second adhesive sheet 2 placed on the base sheet 11 to form an optical film with adhesive sheet 51. The optical film with adhesive sheet 51 includes the base sheet 11, the second adhesive sheet 2, and the optical film 3 in this order. The optical film with adhesive sheet 51 can be used as it is or after the base sheet 11 is peeled off, for example, as an optical laminate including the second adhesive sheet 2 and the optical film 3 in an image display device or the like. The optical laminate may be attached to an object (for example, an image forming panel) via the second adhesive sheet 2. However, the use of the optical film with adhesive sheet 51 is not limited to the above example. An additional member such as an optical film may be placed on the exposed surface 37 formed by peeling off the base sheet 11 from the optical film with adhesive sheet 51. As an example, an optical film with adhesive sheet 52 including the optical film 3A, the second adhesive sheet 2, and the optical film 3B in this order can be formed (see FIG. 6). The optical films 3A and 3B may be the same as or different from each other.
[0093] The optical film 3 may be disposed directly or indirectly on the modified surface 14 and the exposed surface 37. In other words, the optical film 3 may be disposed so as to be in contact with the modified surface 14 or the exposed surface 37, or may be disposed with another layer sandwiched between the modified surface 14 or the exposed surface 37.
[0094] The surface of the optical film 3 that contacts the second pressure-sensitive adhesive sheet 2 may be a surface that has been subjected to a surface modification treatment using active energy rays. This embodiment is particularly suitable for improving the anchoring force between the second pressure-sensitive adhesive sheet 2 and the optical film 3. Examples of the surface modification treatment for the optical film 3 are the same as the examples of the surface modification treatment for the first pressure-sensitive adhesive sheet 1, including preferred examples.
[0095] With reference to FIG. 7, another example of the method for producing an optical film with a pressure-sensitive adhesive sheet of the present invention will be described. In this example, a long optical film 3 is placed on the modified surface 14 of the second pressure-sensitive adhesive sheet 2 formed by the method of FIG. 4 to form a long optical film with a pressure-sensitive adhesive sheet 51. The optical film 3 is unwound from a roll 46 and placed on the modified surface 14. The above steps are performed while the base sheet 31 (11) is being transported. As shown in FIG. 7, the formation of the second pressure-sensitive adhesive sheet 2 and the formation of the optical film with a pressure-sensitive adhesive sheet 51 may be performed continuously. Also, the formation of the first pressure-sensitive adhesive sheet 1, the formation of the second pressure-sensitive adhesive sheet 2, and the formation of the optical film with a pressure-sensitive adhesive sheet 51 may be performed continuously. The method of FIG. 7 is particularly suitable for mass production of the optical film with a pressure-sensitive adhesive sheet 51.
[0096] The optical film 3 is, for example, a film including at least one selected from the group consisting of a polarizing film and a retardation film. The optical film 3 may be a laminated film including a polarizing film and / or a retardation film. The optical film 3 may include a glass film. However, the optical film 3 is not limited to the above examples.
[0097] The polarizing film includes a polarizer. The polarizing film typically includes a polarizer and a protective film (transparent protective film). The protective film is disposed, for example, in contact with the main surface (surface having the widest area) of the polarizer. The polarizer may be disposed between two protective films. The protective film may be disposed on at least one surface of the polarizer.
[0098] The polarizer is not particularly limited, and examples thereof include hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified ethylene-vinyl acetate copolymer films, which are uniaxially stretched after adsorbing dichroic substances such as iodine and dichroic dyes; polyene-based oriented films such as dehydrated polyvinyl alcohol and dehydrochlorinated polyvinyl chloride; etc. Polarizers are typically made of polyvinyl alcohol films (polyvinyl alcohol films include partially saponified ethylene-vinyl acetate copolymer films) and dichroic substances such as iodine.
[0099] The thickness of the polarizer is not particularly limited, and may be, for example, 80 μm or less, 50 μm or less, 30 μm or less, 25 μm or less, or even 20 μm or less. The lower limit of the thickness of the polarizer is not particularly limited, and may be, for example, 1 μm or more, 5 μm or more, 10 μm or more, or even 15 μm or more. A thin polarizer (for example, a thickness of 20 μm or less) is suppressed in dimensional change, and can contribute to improving the durability of the optical laminate, particularly the durability at high temperatures.
[0100] As the material of the protective film, for example, a thermoplastic resin excellent in transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, etc. is used. Specific examples of such thermoplastic resins include cellulose resins such as triacetyl cellulose, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene-based resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The material of the protective film may be a thermosetting resin or an ultraviolet-curing resin such as a (meth)acrylic, urethane, acrylic urethane, epoxy, or silicone-based resin. When the polarizing film has two protective films, the materials of the two protective films may be the same or different from each other. For example, a protective film made of a thermoplastic resin may be bonded to one main surface of the polarizer via an adhesive, and a protective film made of a thermosetting resin or an ultraviolet-curing resin may be bonded to the other main surface of the polarizer. The protective film may contain one or more types of optional additives, such as ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, color inhibitors, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.
[0101] The thickness of the protective film can be appropriately determined, but is generally about 10 to 200 μm in terms of strength, workability such as handleability, thinness, and the like.
[0102] The polarizer and the protective film are usually adhered to each other via a water-based adhesive or the like. Examples of the water-based adhesive include an isocyanate-based adhesive, a polyvinyl alcohol-based adhesive, a gelatin-based adhesive, a vinyl-based latex, a water-based polyurethane, and a water-based polyester. Examples of adhesives other than the above-mentioned adhesives include an ultraviolet-curable adhesive and an electron beam-curable adhesive. The electron beam-curable polarizing plate adhesive exhibits suitable adhesion to various protective films. The adhesive may contain a metal compound filler.
[0103] In the polarizing film, a retardation film or the like can be formed on the polarizer instead of the protective film. Another protective film or a retardation film or the like can be further provided on the protective film.
[0104] The protective film may have a hard coat layer on the surface opposite to the surface bonded to the polarizer, and may also be subjected to treatments for the purposes of anti-reflection, anti-sticking, diffusion, anti-glare, etc.
[0105] The polarizing film may be a circular polarizing film.
[0106] The retardation film may be one obtained by stretching a polymer film or one obtained by aligning and fixing a liquid crystal material. The retardation film has birefringence, for example, in the in-plane and / or thickness direction.
[0107] Retardation films include anti-reflection retardation films (see JP 2012-133303 A,
[0221] ,
[0222] ,
[0228] ), viewing angle compensation retardation films (see JP 2012-133303 A,
[0225] ,
[0226] ), and tilted orientation retardation films for viewing angle compensation (see JP 2012-133303 A,
[0227] ).
[0108] The specific configuration of the retardation film, for example, the retardation value, arrangement angle, three-dimensional birefringence, whether it is a single layer or a multilayer, and the like, are not particularly limited, and any known retardation film can be used.
[0109] The thickness of the retardation film is preferably 20 μm or less, more preferably 10 μm or less, further preferably 1 to 9 μm, and particularly preferably 3 to 8 μm.
[0110] The retardation film may include, for example, a quarter wave plate and / or a half wave plate in which a liquid crystal material is oriented and fixed.
[0111] In the optical films 51 and 52 with adhesive sheet, the anchoring force of the second adhesive sheet 2 to the optical film 3 may be 10N / 25mm or more, or 12N / 25mm or more. In other words, the optical films 51 and 52 with adhesive sheet may be formed in which the anchoring force of the second adhesive sheet 2 to the optical film 3 is 10N / 25mm or more, or even 12N / 25mm or more. The anchoring force may be 13N / 25mm or more, 14N / 25mm or more, 15N / 25mm or more, 16N / 25mm or more, or even 17N / 25mm or more. The upper limit of the anchoring force may be, for example, 50N / 25mm or less, or 30N / 25mm or less. In addition, a film containing a (meth)acrylic resin as a main component (hereinafter, "acrylic film") may be used in the optical film 3 such as a protective film for a polarizer. The adhesive strength between the acrylic film and the adhesive sheet generally tends to be small. From this perspective, second pressure-sensitive adhesive sheet 2 having a second anchoring strength within the above range is particularly suitable for bonding to optical film 3 which is an acrylic film.
[0112] The anchoring force of the second adhesive sheet 2 to the optical film 3 can be measured by the following method. A laminate of the optical film 3 and the second adhesive sheet 2 is cut to a width of 25 mm x length of 150 mm to prepare a test piece. As long as the optical film 3 and the second adhesive sheet 2 are in contact with each other, the laminate may contain other layers. Next, the entire surface of the optical film 3 provided in the test piece is superimposed on a stainless steel test plate via a double-sided tape, and a 2 kg roller is moved back and forth to press them together. Next, the second adhesive sheet 2 provided in the test piece is superimposed on the evaluation sheet, and a 2 kg roller is moved back and forth to press them together. The evaluation sheet is not particularly limited as long as it has a size of 30 mm wide x 150 mm long and does not peel off from the second adhesive sheet 2 during the test. For example, an ITO film (125 Tetolite OES (manufactured by Oike Kogyo Co., Ltd.), etc.) can be used as the evaluation sheet. Next, using a commercially available tensile tester, while holding the evaluation sheet, the second pressure-sensitive adhesive sheet 2 is peeled off from the optical film 3 at a peel angle of 180° and a tensile speed of 300 mm / min, and the average peel force is determined as the anchoring force of the second pressure-sensitive adhesive sheet 2 to the optical film 3. The above test is performed in an atmosphere of 23°C±5°C.
[0113] An image display device may be formed using the optical films 51 and 52 with adhesive sheets. The image display device may be formed, for example, by bonding the optical films 51 and 52 with adhesive sheets to an image display panel. The bonding may be performed using a second adhesive sheet 2. The image display device may be an organic EL display or a liquid crystal display. However, the image display device is not limited to the above examples. The image display device may be an electroluminescence (EL) display, a plasma display (PD), a field emission display (FED: Field Emission Display), or the like. The image display device may be used for home appliances, in-vehicle applications, public information displays (PID), and the like. EXAMPLES
[0114] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the examples shown below.
[0115] [Preparation of monomer syrup] (Synthesis Example 1) 99 parts by weight of n-butyl acrylate (BA), 1 part by weight of 4-hydroxybutyl acrylate (HBA), 0.05 parts by weight of Omnirad184 (1-hydroxycyclohexyl-phenyl ketone, IGM Resins) and 0.05 parts by weight of Omnirad651 (2,2-dimethoxy-1,2-diphenylethan-1-one, IGM Resins) as photopolymerization initiators were placed in a four-bottom flask and irradiated with ultraviolet light under a nitrogen atmosphere to obtain a partially photopolymerized monomer syrup A1. The ultraviolet light irradiation was continued until the viscosity of the liquid in the flask (measurement conditions: BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached approximately 20 Pa·s.
[0116] (Synthesis Example 2) Monomer syrup A2 was prepared in the same manner as Monomer syrup A1, except that the monomers used were changed as shown in Table 1. In addition, "AA" in Table 1 is acrylic acid.
[0117] [Table 1]
[0118] [Preparation of photocurable composition] Photocurable compositions C1 and C2 were obtained by mixing the monomer syrup and the crosslinking agent so as to obtain the compositions shown in Table 2. In addition, "NDDA" in Table 2 is 1,9-nonanediol diacrylate.
[0119] [Table 2]
[0120] [Preparation of the first adhesive sheet] (Production Example 1: Preparation of Release Liner A) Addition reaction curing type silicone (LTC761 containing hexenyl group-containing polyorganosiloxane, 30 wt% toluene solution, manufactured by Dow Corning Toray) 30 parts by weight, release control agent (BY24-856 containing unreactive silicone resin, manufactured by Dow Corning Toray) 0.9 parts by weight, curing catalyst (SRX212 containing platinum catalyst, manufactured by Dow Corning Toray) 2 parts by weight, and toluene / hexane mixed solvent (volume ratio 1: 1) as a dilution solvent were mixed to obtain a silicone-based release agent composition. The concentration of silicone solids in the release agent composition was 1.0 wt%. Next, the release agent composition was applied to one side of a liner substrate (Lumirror XD500P, a polyester film, thickness 75 μm) with a wire bar and heated at 130 ° C for 1 minute to prepare a release liner A having a release layer (thickness 60 nm) on one side.
[0121] (Production Example 2: Production of Release Liner B) A release liner B having a release layer (thickness 120 nm) on one side was prepared in the same manner as in Production Example 1, except that the coating thickness of the release agent composition on the liner substrate was changed.
[0122] (Production Example 3: Preparation of First Adhesive Sheet A) The photocurable composition C1 was applied with an applicator so as to be sandwiched between the release liner A prepared in Production Example 1 and the release liner B prepared in Production Example 2, to obtain a first laminate consisting of the release liner A, the coating layer, and the release liner B. Both release liners A and B were used so that the release layer was in contact with the coating layer. Next, irradiation with light with an intensity of 2.5 mW / cm was applied from the side of the release liner A in the first laminate. 2The coating layer was photocured by irradiating it with ultraviolet light (black light source) under conditions of 100 s, 100 s, and 640 s exposure time to form a second laminate composed of release liner A, first adhesive sheet A (thickness 20 μm) and release liner B. The polymerization rate of the formed first adhesive sheet A was 98.1%. The amount of residual monomer in the formed first adhesive sheet A was 18230 ppm. The amount of residual monomer was evaluated by GC analysis. The amount of residual monomer in the subsequent first adhesive sheet and second adhesive sheet was also evaluated in the same manner. The device and measurement conditions used for the GC analysis are shown below. Equipment used: GC7890A (Agilent Technologies) Column: HP-1 (Agilent Technologies) Detector: Flame ionization detector (FID) ·Inlet temperature: 250℃ Measurement temperature conditions: The following (1) to (4) were carried out in this order: (1) Hold at 0°C for 3 minutes, (2) Raise temperature at a rate of 10°C / min, (3) After reaching 120°C, raise temperature at a rate of 20°C / min, (4) Hold at 300°C. Sample preparation method: 0.05 g of sample (adhesive sheet) was placed in a screw bottle, 2.5 mL of ethyl acetate was added, and the bottle was shaken overnight. The resulting solution was filtered through a 0.45 μm membrane filter, and 1 μL of the filtrate was injected into a GC for analysis.
[0123] (Production Example 4: Preparation of First Adhesive Sheet B) A second laminate composed of release liner A, first pressure-sensitive adhesive sheet B (thickness: 20 μm) and release liner B was formed in the same manner as in Production Example 2, except that photocurable composition C2 was used instead of photocurable composition C1 and the ultraviolet irradiation time was changed to 480 seconds. The polymerization rate of the formed first pressure-sensitive adhesive sheet B was 97.9%. The amount of residual monomer in the first pressure-sensitive adhesive sheet B was 19320 ppm.
[0124] (Production Example 5: Preparation of First Adhesive Sheet C) A second laminate composed of release liner A, first pressure-sensitive adhesive sheet C (thickness: 20 μm) and release liner B was formed in the same manner as in Production Example 2, except that the ultraviolet irradiation time was changed to 2000 seconds. The polymerization rate of the formed first pressure-sensitive adhesive sheet C was 97.7%. The amount of residual monomer in the first pressure-sensitive adhesive sheet C was 1500 ppm.
[0125] [Preparation of the second adhesive sheet] Example 1 The release liner B was peeled off from the second laminate produced in Production Example 3 to expose one side of the first pressure-sensitive adhesive sheet A. Next, the exposed surface of the first pressure-sensitive adhesive sheet A was subjected to a discharge of 14.6 kJ / m in an atmosphere with an oxygen concentration of 0.1% by volume (oxygen-nitrogen mixed atmosphere, 1 atm). 2 A second pressure-sensitive adhesive sheet was obtained by subjecting the sheet to a corona treatment at 800 V. The amount of residual monomer in the obtained second pressure-sensitive adhesive sheet was 2990 ppm.
[0126] (Examples 2 to 9) Second pressure-sensitive adhesive sheets of Examples 2 to 9 were obtained in the same manner as in Example 1, except that the first pressure-sensitive adhesive sheet shown in Table 3 below was subjected to corona treatment under the conditions shown in Table 3. The treatment atmospheres with oxygen concentrations of 1.0 volume %, 0.1 volume % and 0.01 volume % were oxygen-nitrogen mixed atmospheres. The treatment atmosphere with an oxygen concentration of 20.9 volume % was air. The pressure of the treatment atmosphere was 1 atmosphere in all cases.
[0127] Comparative Example 1 A first pressure-sensitive adhesive sheet A obtained by peeling off the release liner B from the second laminate produced in Production Example 2 was used as pressure-sensitive adhesive sheet a of Comparative Example 1 without being subjected to a corona treatment.
[0128] Comparative Example 2 A first pressure-sensitive adhesive sheet C obtained by peeling off the release liner B from the second laminate produced in Production Example 4 was used as pressure-sensitive adhesive sheet b of Comparative Example 2 without being subjected to a corona treatment.
[0129] Comparative Example 3 A first pressure-sensitive adhesive sheet B obtained by peeling off the release liner B from the second laminate produced in Production Example 3 was used as a pressure-sensitive adhesive sheet c of Comparative Example 3 without being subjected to a corona treatment.
[0130] [Table 3]
[0131] [Anchoring power] A polarizing film D1 was placed on the corona-treated surface of the second adhesive sheet prepared in the example and on the exposed surface of the adhesive sheets a to c in the comparative example to prepare an optical laminate. The polarizing film D1 was placed so that the surface of the transparent protective film made of modified methacrylic resin was in contact with the adhesive sheet. Next, the anchoring force between the adhesive sheet and the polarizing film was measured for the prepared optical laminate by the above-mentioned method. The double-sided tape used was a product name "No. 531" manufactured by Nitto Denko Corporation. The stainless steel test plate used was a SUS304 plate (width 40 mm x length 120 mm). The evaluation sheet used an ITO film (125 Tetolite OES, manufactured by Oike Kogyo). The tensile tester used was an autograph SHIMAZU AG-I 10KN (manufactured by Shimadzu Corporation).
[0132] The polarizing film D1 used for the evaluation of anchoring force was prepared as follows. A polyvinyl alcohol film having a thickness of 80 μm was stretched to 3 times while being dyed for 1 minute in an iodine solution having a concentration of 0.3% at a temperature of 30° C. between rolls having different speed ratios. Next, the film was stretched to a total stretching ratio of 6 times while being immersed for 0.5 minutes in an aqueous solution having a temperature of 60° C. and containing boric acid at a concentration of 4% and potassium iodide at a concentration of 10%. Next, the film was immersed for 10 seconds in an aqueous solution having a temperature of 30° C. and containing potassium iodide at a concentration of 1.5% to wash, and then dried at 50° C. for 4 minutes to obtain a polarizer having a thickness of 28 μm. A transparent protective film having a thickness of 30 μm and made of a modified acrylic polymer having a lactone ring structure was attached to one side of the polarizer with a polyvinyl alcohol adhesive. Furthermore, a 47 μm-thick transparent protective film made of a triacetyl cellulose film (Konica Minolta, product name "KC4UY") with a hard coat layer (HC) was attached to the other surface of the polarizer using a polyvinyl alcohol adhesive. Polarizing film D2 was produced by heating and drying for 5 minutes in an oven set at 70°C. Furthermore, a discharge amount of 63 W / (m2) was applied to the surface of polarizing film D2 on the transparent protective film side made of modified acrylic polymer in the air. 2 The corona treatment was carried out for 1 min.
[0133] [Odor] The odor of the second pressure-sensitive adhesive sheet produced in the example and each of the pressure-sensitive adhesive sheets of the comparative example was evaluated as follows.
[0134] 4cm of adhesive sheet to be evaluated 2The sample was placed in an aluminum cup and heated at 40°C for 10 minutes under a nitrogen gas flow using a heating device (MARKES, T-CTE250). All gases generated by heating were passed through an adsorbent and collected. The adsorbent after collecting the gas was heated using a thermal desorption device (MARKES, TD-100) directly connected to a GC / MS device to liberate the collected components. The liberated components were introduced into a GC / MS column, and a sensory test (sniffing GC / MS test) was conducted by three panelists to determine whether the gas separated by the column could be smelled when sniffed. When three panelists judged that they could smell the odor, the panelists were given the grade C, when two panelists judged that they could smell the odor, when one panelist judged that they could smell the odor, the panelists were given the grade B, when one panelist judged that they could smell the odor, and when none panelists judged that they could smell the odor, the panelists were given the grade AA. In addition, the panelists identified the retention time at which the odor peaked when the odor was sensed, and the component that caused the peak was identified by GC / MS analysis. The component that caused the peak was n-butyl acrylate (BA) in all pressure-sensitive adhesive sheets that were rated A, B, or C for odor.
[0135] [Productivity] The productivity of the second pressure-sensitive adhesive sheets produced in the examples and the pressure-sensitive adhesive sheets of the comparative examples was evaluated as follows. A: The case where the time T required for the amount of residual monomer to reach 10,000 ppm or less was 480 seconds or less was rated as A. B: The case where the time T required for the amount of residual monomer to reach 10,000 ppm or less was more than 480 seconds and 960 seconds or less was rated as B. C: A case where the time T required for the residual monomer amount to reach 10,000 ppm or less exceeded 960 seconds, or a case where the residual monomer amount exceeded 10,000 ppm was rated C. Note that time T is the treatment time required for the residual monomer amount to reach 10,000 ppm or less through corona treatment for the second adhesive sheet obtained by corona treatment, and is the ultraviolet ray exposure time required for the residual monomer amount to reach 10,000 ppm or less when forming the second laminate from the first laminate for the adhesive sheet of Comparative Example 2 obtained without corona treatment.
[0136] The evaluation results are shown in Table 4 below, together with the corona treatment conditions and the amount of residual monomer in the second pressure-sensitive adhesive sheet.
[0137] [Table 4] [Industrial Applicability]
[0138] The pressure-sensitive adhesive sheet obtained by the production method of the present invention can be used, for example, in optical laminates and image display devices. [Explanation of symbols]
[0139] 1 First adhesive sheet 2 Second adhesive sheet 3,3A,3B Optical Film 14 Modified surface (surface that has been modified) 21 Active energy rays 32 Coating layer 35 light 51,52 Optical film with adhesive sheet
Claims
1. A method for producing a pressure-sensitive adhesive sheet, comprising: performing a surface modification treatment using active energy rays on a first pressure-sensitive adhesive sheet containing a polymer of a monomer and a residual monomer, thereby obtaining a second pressure-sensitive adhesive sheet in which the amount of the residual monomer is reduced compared to the first pressure-sensitive adhesive sheet.
2. The method for producing a pressure-sensitive adhesive sheet according to claim 1 , wherein the amount of the residual monomer in the second pressure-sensitive adhesive sheet is 5000 ppm (by weight) or less.
3. The method for producing a pressure-sensitive adhesive sheet according to claim 1 , wherein the amount of the residual monomer in the first pressure-sensitive adhesive sheet is 6000 ppm (by weight) or more.
4. The method for producing a pressure-sensitive adhesive sheet according to claim 1 , wherein the surface modification treatment is at least one selected from the group consisting of a corona treatment, a plasma treatment, an excimer UV light treatment, and a frame treatment.
5. The method for producing a pressure-sensitive adhesive sheet according to claim 1 , wherein the surface modification treatment is carried out in an atmosphere having an oxygen concentration of 20% by volume or less.
6. The method for producing a pressure-sensitive adhesive sheet according to claim 5 , wherein the atmosphere is an inert gas atmosphere.
7. The method for producing a pressure-sensitive adhesive sheet according to claim 1 , wherein the surface modification treatment is carried out on an exposed surface of the first pressure-sensitive adhesive sheet.
8. The method for producing a pressure-sensitive adhesive sheet according to claim 1 , wherein the first pressure-sensitive adhesive sheet is formed from a photocurable composition containing a group of monomers and / or a partial polymer of the group of monomers.
9. The method for producing a pressure-sensitive adhesive sheet according to claim 8 , wherein the monomer group includes a (meth)acrylic monomer.
10. The method for producing a pressure-sensitive adhesive sheet according to claim 1 , further comprising forming the first pressure-sensitive adhesive sheet by irradiating a coating layer containing a photocurable composition containing a group of monomers and / or a partial polymer of the group of monomers with light.
11. The method for producing a pressure-sensitive adhesive sheet according to claim 10 , wherein the first pressure-sensitive adhesive sheet is formed by irradiating a laminate comprising a base sheet, the coating layer, and a release liner in this order with the light.
12. The method for producing a pressure-sensitive adhesive sheet according to claim 10 , wherein the light is different from the active energy rays.
13. A method for producing an optical film with an adhesive sheet, comprising: arranging an optical film on a surface of the second adhesive sheet formed by the manufacturing method described in any one of claims 1 to 12 to form an optical film with an adhesive sheet.
14. The method for producing an optical film with a pressure-sensitive adhesive sheet according to claim 13 , wherein the surface is a surface that has been subjected to the surface modification treatment.
15. The method for producing an optical film with a pressure-sensitive adhesive sheet according to claim 13 , wherein the optical film comprises at least one film selected from the group consisting of a polarizing film and a retardation film.
16. The method for producing an optical film with a pressure-sensitive adhesive sheet according to claim 13 , wherein the optical film with a pressure-sensitive adhesive sheet is formed such that the anchoring strength of the second pressure-sensitive adhesive sheet to the optical film is 12 N / 25 mm or more.